Catridecacog: a breakthrough in the treatment of congenital factor XIII A-subunit deficiency? - Korte, Wolfgang (Dove Medical Press, 2014)
Circulating factor XIII (FXIII) consists of two active (A) and two carrier (B) subunits in tetrameric form. Congenital FXIII deficiency is a rare autosomal-recessive trait that mostly results from an FXIII A-subunit deficiency. Classic coagulation assays, such as prothrombin time or activated partial thromboplastin time, are not sensitive to FXIII; therefore, specific FXIII assays are necessary to detect the deficiency. The clinical picture of congenital FXIII deficiency comprises abortions, umbilical cord bleeding, increased surgical bleeding, intracerebral hemorrhage (which can, unfortunately, be the very first sign of severe FXIII deficiency), menorrhagia, and wound-healing disorders. Given the risk of intracranial hemorrhage, continued prophylaxis is to be recommended in severe deficiency, even in the actual absence of bleeding symptoms. Functional FXIII half-life decreases in consumptive processes (eg, surgery), explaining why increased dosing is needed in such situations. A recombinant FXIII (rFXIII) subunit-A molecule, which is expressed in Saccharomyces cerevisiae, has been evaluated for replacement therapy in congenital FXIII deficiency. The bleeding frequency under continued rFXIII prophylaxis during a year-long treatment period was significantly lower compared to on-demand treatment. Importantly, no severe spontaneous bleedings occurred, and bleeding requiring additional intervention only occurred after relevant trauma. Treatment with rFXIII proved to be safe: antibodies against rFXIII detected in four patients were not considered clinically relevant. No allergic reactions were observed. These data show that rFXIII can be used safely and effectively for continued prophylaxis in congenital FXIII deficiency; it is conceivable that this also holds true for treatment of acute bleeding, but clinical proof of this is pending.